Proteoglycans and Glycosaminoglycans in Stem Cell Homeostasis and Bone Tissue Regeneration - Chen, Jiawen; Sun, Tianyu; You, Yan; Wu, Buling; Wang, Xiaofang; Wu, Jingyi (Frontiers in Cell and Developmental Biology, 2021)
Stem cells maintain a subtle balance between self-renew and differentiate under the regulatory network supported by both intracellular and extracellular components. Proteoglycans are large glycoproteins presented abundantly on the cell surface and in the extracellular matrix where they play pivotal roles in facilitating signaling transduction and maintaining stem cell homeostasis. In this review, we outlined the distinct proteoglycans profiles and their functions in the regulation of stem cell homeostasis, as well as recent progresses and prospects of utilizing proteoglycans /glycosaminoglycans as a novel glycomics carrier or bio-active molecules in bone regeneration.